2013
DOI: 10.1080/13676261.2012.725839
|View full text |Cite
|
Sign up to set email alerts
|

Couch surfing on the margins: the reliance on temporary living arrangements as a form of homelessness amongst school-aged home leavers

Abstract: This paper examines couch surfing as a form of youth homelessness. The focus is on adolescents who do not have support from parental homes and who frequently move from one temporary living arrangement to another, without a secure 'place to be'. Drawing on the findings of sociological research with a group of young couch surfers in Australia, the aim is to unpack the marginalising social processes that produce this practice as an outcome of early home leaving. Contrary to the view that adolescent couch surfers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
2

Year Published

2015
2015
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 30 publications
1
34
0
2
Order By: Relevance
“…Secondly, EU-SILC data only includes household members who reside longer than 6 months and therefore the analysis excludes very short-term co-residence or sharing; thus likely underestimating total semidependence levels as previous research has identified common practices of temporary sharing (i.e. 'couch surfing') where other avenues of state or family support are not available (McLoughlin, 2013). Thirdly, the study focuses on welfare regime and housing system contexts and does not purport to look at an exhaustive list of potential factors.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, EU-SILC data only includes household members who reside longer than 6 months and therefore the analysis excludes very short-term co-residence or sharing; thus likely underestimating total semidependence levels as previous research has identified common practices of temporary sharing (i.e. 'couch surfing') where other avenues of state or family support are not available (McLoughlin, 2013). Thirdly, the study focuses on welfare regime and housing system contexts and does not purport to look at an exhaustive list of potential factors.…”
Section: Limitationsmentioning
confidence: 99%
“…Extended co-residence or returns to the parental home seem to play an increasingly important role in many countries (Lennartz et al, 2014) and, outside the natal home, non-traditional forms of sharing might also represent a significant short or longerterm option. Shared housing can be a coping mechanism where other forms of family or state support are not available and can range from the informal and transitory, such as in 'couch surfing' (McLoughlin, 2013), to being a longer-term strategy. Shared housing with strangers, friends, or other relatives can represent exactly the type of intermediary (in)dependence that can provide partial autonomy where economic conditions do not allow for fully independent housing status or -as a lifestyle choice -where continued social support is desired within the housing arrangement.…”
Section: Semi-dependent Housing and Emerging Adulthoodmentioning
confidence: 99%
“…A lack of consensus and consistency on what constitutes homelessness among unaccompanied youth, and how to measure it, poses a significant part of the challenge (Toro, Dworsky & Fowler, ). Couch surfing often lies at the center of this ambiguity (McLoughlin, ). The term refers to young people without support from parental homes who frequently “move from one temporary living arrangement to another, without a secure ‘place to be’” (McLoughlin, , p. 521).…”
Section: Introductionmentioning
confidence: 99%
“…Research on couch surfing in homeless youth populations reveals that it often involves staying at friends' houses or moving between temporary forms of accommodation with typically rent-free arrangements (McLoughlin, 2013). It often occurs because young people are running away from a problem at home (Thielking, Flatau, La Sala & Sutton, 2015).…”
Section: Couch Surfingmentioning
confidence: 99%
“…Couch surfing contradicts the stereotypical idea of a 'street kid' that most Australians associate with youth homelessness (Homelessness Australia, 2014). It represents a largely hidden form of homelessness and has, in many ways, been excluded from the wealth of research conducted on homeless youth (McLoughlin, 2013).…”
Section: Couch Surfingmentioning
confidence: 99%